Stereoselective Polymer-Supported Synthesis of Morpholine- and Thiomorpholine-3-carboxylic Acid Derivatives - Králová, Petra; Fülöpová, Veronika; Maloň, Michal; Volná, Tereza; Popa, Igor; Soural, Miroslav (ACS combinatorial science, 2017)
Herein we report the polymer-supported synthesis of 3,4-dihydro-2H-1,4-oxazine-3-carboxylic acid derivatives using immobilized Fmoc-Ser(tBu)-OH and Fmoc-Thr(tBu)-OH as the starting materials. After the solid-phase-synthesis of N-alkyl-N-sulfonyl/acyl intermediates, the target dihydrooxazines were obtained using trifluoroacetic acid-mediated cleavage from the resin. This approach was also studied for the preparation of dihydrothiazines from immobilized Fmoc-Cys(Trt)-OH. Inclusion of triethylsilane in the cleavage cocktail resulted in the stereoselective formation of the corresponding morpholine/thiomorpholine-3-carboxylic acids. Stereochemical studies revealed the specific configuration of the newly formed stereocenter and also the formation of stable N-acylmorpholine rotamers.
Keywords: stereoizomerie; Morpholines; morfoliny; Thiazines; oxazine; fluoreny; solid-phase synthesis; Carboxylic Acids; techniky syntézy na pevné fázi; morpholine; kyseliny karboxylové; stereoselective synthesis; Solid-Phase Synthesis Techniques; Stereoisomerism; oxaziny; thiazine; polymery; Polymers; Oxazines; bromoketone; thiaziny; Fluorenes; amino acid; thiomorpholine; nitrobenzenesulfonyl chloride